Penegakan Hukum terhadap Tindak Pidana Penelantaran Anak di Kepolisian Resor Kota Besar Palembang dalam Perspektif Hukum Pidana Islam - Ike Vuspasari; Ema Fathimah; Muhammad Sadi Is (Journal of Sharia and Legal Science, 2026)
Child protection is an important indicator of a state based on the rule of law, but child neglect still occurs in various regions, including Palembang City. This study aims to analyze the implementation of law enforcement against child neglect crimes in the Palembang City Police Resort and its compliance with the principles of Islamic criminal law. The method used is empirical juridical with a qualitative approach through interviews with the Women and Children's Service Unit of the Palembang City Police and analysis of legal documents. The results of the study indicate that law enforcement is carried out through two approaches: penal through investigation and inquiry, and non-penal through counseling, education, and cross-sectoral cooperation. Child neglect is understood multidimensionally, encompassing physical, educational, emotional, and health factors influenced by economic factors, family dysfunction, and low parenting capacity. From the perspective of Islamic criminal law, this strategy is in line with the objectives of maqāṣid al-syarī‘ah, especially ḥifẓ al-nafs, ḥifẓ al-‘aql, and ḥifẓ al-nasl. Child neglect is a form of ta'zir crime, the handling of which is not only repressive but also educational and preventive, based on the principle of sadd al-dharī'ah. This research confirms that the effectiveness of law enforcement is not only measured by the number of cases, but also by the legal system's ability to protect children's rights in accordance with public welfare values. Strengthening synergy between the police, local governments, and child protection agencies, as well as the development of sharia-based standard operating procedures (SOPs), is needed.